Ultrasound-Stimulated Microbubbles Inhibit Aggressive Phenotypes and Promotes Radiosensitivity of esophageal squamous cell carcinoma. Issue 1 (1st January 2021) - Shi, Jinjun; Fu, Chenchun; Su, Xiangyu; Feng, Shicheng; Wang, Sheng
ABSTRACT: Ultrasound (US) is reported to improve the delivery efficiency of drugs loading onto large nanoparticles due to the sonoporation effect. Microbubbles (MBs) can be used as contrast agents of US expanding and contracting under low-amplitude US pressure waves. Ultrasound-stimulated microbubbles (USMBs) therapy is a promising option for the treatment of various cancers as a radiosensitizer. However, its role in esophageal squamous cell carcinoma (ESCC) remains unknown. In our study, human ESCC cell lines (KYSE-410, KYSE-1140) were treated with radiation solely, US alone, or radiation in combination with US or USMBs. The migration and invasion abilities of ESCC cells were examined by wound healing and Transwell assays. ESCC cell apoptosis was assessed using flow cytometry analysis and TUNEL assays. The levels of proteins associated with cell apoptosis and angiogenesis were measured by western blot analysis. A tube formation assay was performed to detect the ESCC cell angiogenesis. We found that USMBs at high levels most effectively most efficiently enhanced the effect of radiation, and significant changes in the viability (48%-51%), proliferation (1%), migration (63%-71%), invasion (52%) and cell apoptosis (31%-50%) of ESCC cells were observed compared with the control group in vitro. The ESCC angiogenesis was inhibited by US or radiation treatment and further inhibited by a combination of radiation and US or USMBs. USMBs at high levels most effectively enhanced the inhibitory effect of radiotherapy on ESCC cell apoptosis. Overall, USMBs enhanced the radiosensitivity of esophageal squamous cell carcinoma cells. Graphical abstract USMBs treatment enhanced the anti-tumor effect of radiation on ESCC cell proliferation, migration, invasion, angiogenesis and apoptosis in vitro. 1USMBs enhance the radiation-induced inhibition on ESCC cell growth 2USMBs promote the radiation effect on ESCC cell apoptosis 3USMBs enhance radiation-caused suppression on ESCC cell migration and invasion 4USMBs enhance the suppression of radiation on ESCC angiogenesis uf0001